If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4m + 15 = 6m + -17 Reorder the terms: 15 + 4m = 6m + -17 Reorder the terms: 15 + 4m = -17 + 6m Solving 15 + 4m = -17 + 6m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-6m' to each side of the equation. 15 + 4m + -6m = -17 + 6m + -6m Combine like terms: 4m + -6m = -2m 15 + -2m = -17 + 6m + -6m Combine like terms: 6m + -6m = 0 15 + -2m = -17 + 0 15 + -2m = -17 Add '-15' to each side of the equation. 15 + -15 + -2m = -17 + -15 Combine like terms: 15 + -15 = 0 0 + -2m = -17 + -15 -2m = -17 + -15 Combine like terms: -17 + -15 = -32 -2m = -32 Divide each side by '-2'. m = 16 Simplifying m = 16
| -11+9u=18u-1-14u | | -4+7q=8q-7-3 | | 0.5k+1.5=3 | | -4-t=-4+t | | 3x+7=7x+15 | | 15/6=n/12 | | 0.6x+2=0.7+2 | | -10-7w-10=7-4w | | 4-3cot=1 | | 40=8(x-8) | | X^2-12X-4.5=0 | | P=2x+3 | | -8y=-6-9y | | -3(5+2x)=-2x+13 | | 8-(4x-12)=8x-(3x-2) | | 2-5f=-7f+10 | | 4+2y=10-4y | | 3/5=6n | | -j=j-8 | | -5x(4x-8y^2+4)= | | 10-6n=-6-10n | | 3b-11=3+b | | 7x-14=7(x+4) | | 5+10d=9d | | 6x-(10-2x)=3x+5 | | 9b+3=22 | | 18.9125-(1/4)= | | 9b+3=20 | | 9b+3=19 | | 2x^3-11x^2-10x+75=0 | | 9b+3=18 | | 9b+3=16 |